Toward an ensemble view of chromatosome structure: a paradigm shift from one to many - Öztürk, Mehmet Ali; Cojocaru, Vlad; Wade, Rebecca C. (Structure, 2018)
There is renewed interest in linker histone (LH)—nucleosome binding and how LHs influence eukaryotic DNA compaction. For a long time, the goal was to uncover “the structure of the chromatosome,” but recent studies of LH-nucleosome complexes have revealed an ensemble of structures. Notably, the reconstituted LH-nucleosome complexes used in experiments rarely correspond to the sequence combinations present in organisms. For a full understanding of the determinants of the distribution of the chromatosome structural ensemble, studies must include a complete description of the sequences and experimental conditions used, and be designed to enable systematic evaluation of sequence and environmental effects.